RANCANG BANGUN WATER INJECTION BERBASIS MIKROKONTROLER SERTA PENGARUHNYA TERHADAP TORSI DAN DAYA PADA SEPEDA MOTOR HONDA MEGA PRO TAHUN 2009 - Mahmud, Fauzianto (Jurnal Nosel, 2015)
The purposes of this research are: (1) To develop and to design microcontroller-based system of water injection on Honda Mega Pro Motorcycle 2009. (2) To know the effect that uses microcontroller-based water injection of torque and power on Honda Mega Pro motorcycle 2009. (3) To know the quantity of torque and power on Honda Mega Pro motorcycle 2009 that uses microcontroller-based water injection.This research used descriptive quantitative methods. The sample of the research used is Honda Mega Pro 2009 in KC11E1237512 engine serial number. The data retrieved from the quantity of torque and power by using water microcontroller-based water injection with composition on (A100, A90, A80, A70, A60, and A50). The data are retrieved from the result of the research which are put into table and presented in the graphic form and then being analyzed.Based on the result of the research, it can be concluded that: (1) Development and design of microcontroller-based water injection can work and operate properly on Honda Mega Pro motorcycle 2009. (2) There was a positive effect that uses microcontroller-based water injection of torque and power on Honda Mega Pro motorcycle 2009. (3) The best maximal torque is produced by using water injection (A50) on 14.29 Nm at 6250 rpm engine speeds or the torque escalates 1.11 Nm or 8.42% and the worst maximal torque is produced by using water injection (A100) on 13.07 Nm at 6162 rpm engine speeds or the torque decreases 0.11 Nm or 0.83% compared to the maximal torque produced by motorcycle without water injection (standard) on 13.18 Nm at 6750 rpm engine speeds. (4) The best maximal power is produced by using water injection (A50) on 13.70 HP at7724 rpm engine speed or the power escalates 0.93 HP or 7.28% and the worst maximal power is produced by using water injection (A100) on 12.43 HP at 7049 rpm engine speeds or the power decreases 0.34 HP or 2.66% compared to the maximal power produced by motorcycle without water injection (standard) on 12.77 HP at 7156 rpm engine speeds.